Quantum Key Distribution for Sustainable and Secure Communication: Opportunities and Challenges - Shashank Thakur (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2023)
This research paper offers an in-depth analysis of the potential benefits of quantum key distribution (QKD) to provide secure communication channels. The limitations of classical cryptography are explored in detail, highlighting the need for alternative approaches to mitigate against the growing sophistication of cyber threats. The advantages of QKD, including its absolute security and ability to detect eavesdropping, are also extensively discussed, along with successful case studies of QKD deployments and critical lessons learned from these initiatives. Despite its potential advantages, the paper also acknowledges the challenges and limitations of practically implementing QKD in its scalability, cost, interoperability, susceptibility to quantum attacks, and the importance of investment in research and development to accelerate progress in this field. Additionally, the paper examines successful implementations of QKD in real-life scenarios. The potential applications of QKD in various sectors, such as government and military, healthcare, and finance, are highlighted. The regulatory and legal challenges surrounding using QKD protocol encryption, including the need for licensing and approval, are also briefly discussed. In conclusion, the paper discusses future opportunities and challenges for quantum cryptography and QKD in achieving sustainable and secure communication and the prospects of practical implementation of QKD. To address the challenges and promote QKD deployment in sustainable communication networks, this paper recommends increasing funding for continuing QKD research and development; international collaboration between academia and industry; stakeholder engagement to ensure QKD's safe, secure, and ethical deployment; and the incentivization of QKD deployment in critical infrastructure. Additionally, governments should prioritize QKD research and education programs to create a skilled workforce in developing and deploying QKD technology. Overall, the findings of this research demonstrate the need for more research, development, and policy recommendations to enable the practical deployment of QKD in sustainable communication networks and ensure their security and resilience.